Pengaruh Kualitas Produk, Kualitas Pelayanan dan Pemasaran Digital Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan di Apartemen Kemang Grup PT Pudjiadi Prestige Tbk Jakarta - Anis Rostiani; Rahayu Lestari; Andini Nurwulandari (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this research are to analysis effect of product quality, quality of service and digital marketing to customer loyalty through customer satisfaction. 150 people for sampel from tenant and People who have ever rented on Kemang Apartment Group PT Pudjiadi Prestige Tbk. Data were collected by questionnaires and Structural Equation Model (SEM) were applies as an analysis technique. The results analysis showed that product quality, quality of service and digital marketing positive effect on customer loyalty through customer satisfaction. The Implication is product quality, quality of service and digital marketing need to be increased in order to improve customer loyalty through customer satisfaction.